Uptake of COVID-19 vaccination in people with blood cancer: population-level cohort study of 12 million patients in England - Hirst, J; Mi, E; Copland, E; Patone, M; Coupland, C; Hippisley-Cox, J (Elsevier, 2023)
Background: People with blood cancers have increased risk of severe outcomes from COVID-19 and were prioritised for vaccination.